Non-linear economic model predictive control of water distribution networks. (August 2017) - Wang, Ye; Puig, Vicenç; Cembrano, Gabriela
Abstract : Highlights: Non-linear economic model predictive control (NEMPC) of water distribution networks is proposed. Non-linear hydraulic model of the water distribution network is used. A pumping scheduling approach (PSA) is proposed for dealing with ON-OFF pump operations. A two-layer control scheme including NEMPC and PSA is addressed. On-line simulation results of the D-Town water networks with the EPANET hydraulic simulator are provided. Abstract: This paper addresses a non-linear economic model predictive control (EMPC) strategy for water distribution networks (WDNs). A WDN could be considered as a non-linear system described by differential-algebraic equations (DAEs) when flow and hydraulic head equations are considered. As in other process industries, the main operational goal of WDNs is the minimisation of the economic costs associated to pumping and water treatment, while guaranteeing water supply with required flows and pressures at all the control/demand nodes in the network. Other operational goals related to safety and reliability are usually sought. From a control point of view, EMPC is a suitable control strategy for WDNs since the optimal operation of the network cannot be established a priori by fixing reference volumes in the tanks. Alternatively, the EMPC strategy should determine the optimal filling/emptying sequence of the tanks taking into account that electricity price varies between day and night and that the demand also follows a 24-hour repetitive pattern. On the other hand, as a result of the ON/OFF operation of parallel pumps in pumping stations, a two-layer control scheme has been used: a non-linear EMPC strategy with hourly control interval is chosen in the upper layer and a pump scheduling approach with one-minute sampling time in the lower layer. Finally, closed-loop simulation results of applying the proposed control strategy to the D-Town water network are shown.